GM1 Gangliosidosis—A Mini-Review - Nicoli, Elena-Raluca; Annunziata, Ida; d’Azzo, Alessandra; Platt, Frances M.; Tifft, Cynthia J.; Stepien, Karolina M. (Frontiers in Genetics, 2021)
GM1 gangliosidosis is a progressive, neurosomatic, lysosomal storage disorder caused by mutations in the GLB1 gene encoding the enzyme β-galactosidase. Absent or reduced β-galactosidase activity leads to the accumulation of β-linked galactose-containing glycoconjugates including the glycosphingolipid (GSL) GM1-ganglioside in neuronal tissue. GM1-gangliosidosis is classified into three forms (Type I (infantile), Type II (late-infantile and juvenile) and Type III (adult)), based on the age of onset of clinical symptoms, although the disorder is really a continuum that correlates only partially with the levels of residual enzyme activity. Severe neurocognitive decline is a feature of Type I and II disease and is associated with premature mortality. Most of the disease-causing β-galactosidase mutations reported in the literature are clustered in exons 2, 6, 15 and 16 of the GLB1 gene. There are five mouse models of GM1-gangliosidosis reported in the literature generated using different targeting strategies of the Glb1 murine locus. Individual models differ in terms of age of onset of the clinical, biochemical, and pathological signs and symptoms, and overall lifespan. However, they do share the major abnormalities and neurological symptoms that are characteristic of the most severe forms of GM1-gangliosidosis. These mouse models have been used to study pathogenic mechanisms, to identify biomarkers, and to evaluate therapeutic strategies. Three GLB1 gene therapy trials are currently recruiting Type I and Type II patients (NCT04273269, NCT03952637, and NCT04713475) and Type II and Type III patients are being recruited for a trial utilizing the glucosylceramide synthase inhibitor, venglustat (NCT04221451).